Specific Characteristics Of Educational Work At General Education Levels (In the Example of the Activity of the Class Leader) - Nurseit Alijanugli Beketov (Academia One Publishing, 2023)
The institute of class leaders, which has been introduced in the educational institutions of our country and has several decades of development, is justifying itself in a certain sense. However, the fact that an alternative form of position has not been introduced in general education schools to this day gives an opportunity to draw certain positive conclusions about this position. In addition to the educational tasks performed by teachers, parents in the family, and the general public in public schools, class leaders ensure the harmony of the class they lead, actively involve them in learning and educational processes, and ensure the unity of the school, family, and public influence on the student. they are coming. Heads of the class are helping the class team to gather life experiences, master social moral standards, and educate the personality of the student who has matured and educated in all aspects, who has the great goal of serving the Motherland in his heart.
Keywords: Class leaders; education; pedagogy; spirituality